4H‐SiC: a new nonlinear material for midinfrared lasers. Issue 5 (19th July 2013) - Wang, Shunchong; Zhan, Minjie; Wang, Gang; Xuan, Hongwen; Zhang, Wei; Liu, Chunjun; Xu, Chunhua; Liu, Yu; Wei, Zhiyi; Chen, Xiaolong
<x xml:space="preserve">Abstract</x> Nonlinear optical (NLO) frequency conversion is commonly used for generating midinfrared (MIR) lasers that offer light sources for a variety of applications. However, the low laser damage thresholds of NLO crystals used so far seriously limit the output power of MIR lasers. Here, a new nonlinear material 4H‐SiC is demonstrated for producing MIR laser. Broadband MIR radiation ranging from 3.90 to 5.60 μm is generated in 4H‐SiC by phase‐matched difference‐frequency generation for the first time. The results may open a door to practically utilize wide‐bandgap semiconductors with high laser damage thresholds as NLO materials for high power output of MIR lasers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>